Knowledge, Attitude and Practices Towards Lifestyle Related Non-Communicable Diseases (NCDs): A Cross Sectional Study among Indigenous Orang Asli Adults in Negeri Sembilan, Malaysia - M, Ithnin; NAUM , Nor; N, Juliana; NM, Effendy; MA, Sahar; KHA, Abdullah; MSM, Aris; MDM, Rani (IIUM Medical Journal Malaysia, 2020)
INTRODUCTION: An increase in the prevalence of non-communicable diseases (NCDs) among Orang Asli in Malaysia was reported to be associated with their lifestyle changes. This study aimed to determine the level of knowledge, attitude, and practice (KAP) on NCDs among the Orang Asli community and its association with demographic factors of gender, age, and education level. MATERIAL AND METHODS: A cross-sectional study among consented adult Orang Asli in Jelebu, Negeri Sembilan, was conducted by a face-to-face interview using a validated questionnaire. Their knowledge, attitude, and practice on selected NCD risk factors, complications, and treatment was recorded. Bivariate analysis was performed to test the association between their demographic profile and KAP score. RESULTS: A total of 325 respondents with a mean age of 39.9 (±13.2) ranged from 18 to 83 years old participated in this study. Majority of the participants (72.3%) had inadequate knowledge. Despite the inadequacy, they have a good attitude (72.3%) and a moderate practice level (63.4%). Respondents with higher education backgrounds had significantly better knowledge scores compared to lower education background (p<0.001). Female respondents had better practice scores than male respondents (p=0.001). CONCLUSIONS: The study shows that the level of knowledge on NCDs among Orang Asli is low with a moderately healthy lifestyle. Improving the Orang Asli understanding of NCDs prevention by incorporating health programs regularly in their community is a strategic method to increase their awareness. Hence, escalating their good practice on NCDs and eventually their health.